PENGARUH PENDIDIKAN KEUANGAN KELUARGA DAN PENGETAHUAN KEUANGAN TERHADAP PERILAKU MENABUNG SISWA KELAS XI KOMPETENSI KEAHLIAN AKUNTANSI DI SMK NEGERI 1 SURAKARTA - Hapsari Rahayu, Melati; Siswandari; Ivada, Elvia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Saving behavior is one of the essential financial behaviors that should be developed from an early age to support individuals in managing their financial resources responsibly. This study aimed to examine the influence of family financial education and financial knowledge on the saving behavior of eleventh-grade Accounting students at SMK Negeri 1 Surakarta. The research employed a quantitative approach using a survey method. The population consisted of 83 students, and proportional random sampling was applied to determine the research sample. Data were collected through questionnaires and financial knowledge tests. Data analysis included descriptive statistics, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination using IBM SPSS Statistics. The findings revealed that family financial education had no significant effect on students' saving behavior, whereas financial knowledge had a positive and significant effect. Simultaneously, family financial education and financial knowledge significantly influenced saving behavior. The adjusted R² value of 0.189 indicates that the independent variables explained 18.9% of the variation in saving behavior, while the remaining 81.1% was explained by other variables outside the research model. These findings indicate that financial knowledge plays a more dominant role than family financial education in shaping students' saving behavior.